A building information modeling-based tool for estimating building demolition waste and evaluating its environmental impacts. (October 2021) - Su, Shu; Li, Shimeng; Ju, Jingyi; Wang, Qian; Xu, Zhao
Highlights: A BIM-based estimation and evaluation system for demolition waste is developed. Automated waste estimation and impact evaluation in the design stage is achieved. The applicability of the evaluation system is demonstrated by a case study. The integration of BIM, GIS, and LCA for waste management is proved to be effective. Abstract: The amount of building demolition waste produced in China is large, and waste treatment processes discharge many pollutants. Pre-evaluating waste's environmental damage at the design stage of building projects could provide an opportunity to understand and minimize potential environmental impacts. Tools that can conveniently estimate the amount of demolition waste and quantify its impacts are lacking. This study combines building information modeling (BIM), geographic information system (GIS), and life cycle assessment (LCA) to develop an estimation and evaluation system for building demolition waste. In this system, BIM digitizes the specific characteristics of the evaluated buildings and provides geometric and semantic information for waste estimation. GIS offers geographic information regarding waste treatment plants and landfill site, and is used to design waste transportation routes. LCA provides an environmental impact assessment framework and quantifies ecological damage impacts and resource depletion impacts due to demolition waste. The system includes five modules, which form the basis of an automated calculation tool. The evaluation tool can quickly quantify the amount of waste and assess its impacts, while achieving automated waste estimation and impact evaluation after a building is designed. A building in a middle school is taken as a case study to demonstrate and verify the system. This study provides an operable tool for waste evaluation and management at the design stage. With the increasing application of BIM technology in the construction industry, this tool is expected to gain popularity and promote efficient waste management.